Modeling the influence of interleaf layers in composite materials on elastic properties, thermal expansion, and chemical shrinkage. (July 2019) - Frerich, Tim; Brauner, Christian; Jendrny, Jörg; Hermann, Axel S.
Within this paper, it is shown that the assumption of transversal isotropy usually applied to unidirectional layers is not valid, if interleaf layers are introduced to increase the impact performance of the material. An approach is suggested to consider the meso-structure of composite materials with interleaf layers in the calculation of the elastic properties, the thermal expansion coefficients, and the chemical shrinkage coefficients. The approach uses known rules of mixture in a first step, to determine the properties of the carbon fiber–reinforced polymer layer as well as those of the interleaf layer and combine them in a second step by new meso-scale rules of mixture. The approach is discussed using known material data and shows to provide plausible results. The effects of the material properties influenced by the meso-scale rules of mixture on the process induced distortions are then discussed exemplary considering the thermally induced spring-in. It is shown that the meso-structure has a considerable influence on the process-induced distortions and cannot be neglected in the prediction of it.